If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9 = 27 + -9x Reorder the terms: 9 + 3x = 27 + -9x Solving 9 + 3x = 27 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 9 + 3x + 9x = 27 + -9x + 9x Combine like terms: 3x + 9x = 12x 9 + 12x = 27 + -9x + 9x Combine like terms: -9x + 9x = 0 9 + 12x = 27 + 0 9 + 12x = 27 Add '-9' to each side of the equation. 9 + -9 + 12x = 27 + -9 Combine like terms: 9 + -9 = 0 0 + 12x = 27 + -9 12x = 27 + -9 Combine like terms: 27 + -9 = 18 12x = 18 Divide each side by '12'. x = 1.5 Simplifying x = 1.5
| a^2-a+156= | | 36-4g=8 | | -7n-5+2n-5(5n+1)=0 | | 4x+10=10-6x | | 3x-10=5x-10 | | 5+11x=95 | | (5+2i)+(3+6i)= | | q-5-2=7-q | | 12+2.4c=22.5 | | 42=-3(1+5x)-3(3x+1) | | 22*16= | | 1.3=5980000000000000000000000000/x | | 5x+15(22+9x)=50 | | (x-2)*180=3240 | | 2sin^2x=-sinx | | 1-cos(t)=1.5 | | 1-cos(2t)=1.5 | | 3(4x+5)+2(x-7)+6x= | | 16x^5=81x | | x^6+8x^3+16=0 | | y-6=-3(x-4) | | f(t)=-5t+20t+60 | | 5(-7)-2(-3)= | | -30a-5a= | | -5=-11u | | 3x^2+5xy+y^2-4=0 | | x+9+x= | | Log(x)=3.4 | | 8-6(1-9f)=-30 | | ab=5-5c | | 4r^4-8r^2+16= | | 0.3(3x-12)+11=1+1.5x |